2016
DOI: 10.1521/pedi_2015_29_195
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Recognition of Borderline Personality Disorder in a Bipolar World

Abstract: Both bipolar disorder and borderline personality disorder (BPD) are serious mental health disorders resulting in significant psychosocial morbidity, reduced health-related quality of life, and excess mortality. Yet research on BPD has received much less funding from the National Institute of Health (NIH) than has bipolar disorder during the past 25 years. Why hasn't the level of NIH research funding for BPD been commensurate with the level of psychosocial morbidity, mortality, and health expenditures associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 113 publications
0
12
0
Order By: Relevance
“…Several review articles and commentaries about the importance of recognizing bipolar disorder in patients presenting for the treatment of depression have been published in peer reviewed journals (Bowden, 2001; Hirschfeld & Vornik, 2004; Ketter, 2011; McIntyre, 2014; Yatham, 2005). Much less has been written about the importance of improving the recognition of BPD (Zimmerman, 2016). Just as it is important for clinicians to include questions to screen for a history of manic or hypomanic episodes in their evaluation of depressed patients, it is important to screen for the presence of BPD in patients with mood disorders (Zimmerman, Balling, Dalrymple, & Chelminski, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several review articles and commentaries about the importance of recognizing bipolar disorder in patients presenting for the treatment of depression have been published in peer reviewed journals (Bowden, 2001; Hirschfeld & Vornik, 2004; Ketter, 2011; McIntyre, 2014; Yatham, 2005). Much less has been written about the importance of improving the recognition of BPD (Zimmerman, 2016). Just as it is important for clinicians to include questions to screen for a history of manic or hypomanic episodes in their evaluation of depressed patients, it is important to screen for the presence of BPD in patients with mood disorders (Zimmerman, Balling, Dalrymple, & Chelminski, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Second, when using only a clinical diagnostic approach, there may be a variation regarding which disorders are more likely to be diagnosed and which may be overlooked. This may be based on factors such as symptom severity, expectation of response to treatment, or familiarity with particular PD diagnoses (Zimmerman and Morgan, 2013; Zimmerman, 2016). Finally, most prior personality studies have used a categorical diagnostic approach for PD diagnosis, which has been criticized for its questionable validity (Haslam et al ., 2012; Skodol, 2012; Tyrer et al ., 2015).…”
Section: Limitationsmentioning
confidence: 99%
“…Several studies have indicated an improvement in borderline symptoms in response to conventional mood stabilizers but some reports have pointed out the efficacy of SGAs (such as olanzapine, risperidone, paliperidone, aripiprazole etc.) in the control of some symptoms (i.e., psychotic symptoms, dissociation episodes, impulsive behavioral dyscontrol) that do not adequately respond to conventional mood stabilizers (including lithium) [21][22][23][24]. Despite this, it is worthy to note that the PD-BD comorbidity may further decrease treatment adherence and, therefore, the use of a SGA-LAI may improve the compliance and the overall outcomes in such cases [25][26][27][28].…”
Section: Some Critical Challenges In the Contemporary Clinical Intervmentioning
confidence: 99%